1965
DOI: 10.1073/pnas.54.3.869
|View full text |Cite
|
Sign up to set email alerts
|

Water as the source of oxidant and reductant in bacterial chemosynthesis.

Abstract: The two vital aspects of chemoautotrophic metabolism are the generation of energy (ATP or the equivalent) and a simultaneous production of reducing power coupled to the enzymic oxidation of an inorganic substrate. Aleem and Nason' reported that in the obligately chemoautotrophic bacterial genus Nitrobacter the enzymic oxidation of nitrite is catalyzed by a cytochrome-containing electron transport particle via cytochrome c and cytochrome oxidase-like components.They subsequently demonstrated2 the coupling of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 4 publications
0
31
0
Order By: Relevance
“…However, the microbial end-member is not as easily determined from field samples, which usually contain a mixture of nitrate from both sources. Laboratory studies have shown that, during the conversion of ammonium to nitrate by chemolithoautotrophic bacteria, two oxygens come from water and one from O 2 (Aleem et al, 1965;Andersson and Hooper, 1983;Kumar et al, 1983;Hollocher, 1984 (Kendall, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, the microbial end-member is not as easily determined from field samples, which usually contain a mixture of nitrate from both sources. Laboratory studies have shown that, during the conversion of ammonium to nitrate by chemolithoautotrophic bacteria, two oxygens come from water and one from O 2 (Aleem et al, 1965;Andersson and Hooper, 1983;Kumar et al, 1983;Hollocher, 1984 (Kendall, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…During the conversion of ammonium to nitrate by chemolithoautotrophic bacteria, two oxygen atoms originate from H 2 O and one from O 2 (Aleem et al, 1965;Andersson and Hooper, 1983;Kumar et al, 1983). In recent laboratory studies, the kinetic isotope effects during incorporation of O atoms were estimated to be +20.4 ± 2.3 ‰ for ammonia oxidation (O 2 plus H 2 O incorporation) and +8.6 ± 2.3 ‰ for incorporation of H 2 O during nitrite oxidation (Buchwald et al, 2012).…”
Section: δ 18 O and δ 15 N Values Of Atmospheric Nitratementioning
confidence: 99%
“…The findings of Aleem et al (1965), Hollocher et al (1981), Andersson and Hooper (1983) and Kumar et al (1983) suggested that nitrification process incorporates two H 2 O-derived and one O 2 -derived oxygen atom to 385 form nitrate. Further, these studies reported no isotopic effect during oxygen incorporations or any further isotopic exchange.…”
Section: Stable Isotope Composition Of Microbial-nitratementioning
confidence: 99%